Engineering Performance and Cost Evaluation of PET and LDPE-Based Plastic–Sand Interlocking Blocks for Sustainable Construction - Dauda Ali; Auwal Shuaibu (Nusantara Civil Engineering Journal, 2026)
The increasing accumulation of plastic waste and the rising cost of conventional construction materials have necessitated the development of sustainable alternatives. This study investigates the production, performance, and economic viability of interlocking paving blocks made from waste Polyethylene Terephthalate (PET) and Low-Density Polyethylene (LDPE) combined with sand. Plastic waste sourced from residential areas, campuses, and waste centers was processed and used as a complete binder in a plastic–sand composite at a ratio of 1:3. The produced blocks were tested for compressive strength and compared with conventional concrete interlocks. Results show that PET-based blocks achieved an average compressive strength of 4.65 N/mm², while LDPE blocks recorded 3.56 N/mm². A cost analysis revealed that plastic–sand interlocks are significantly cheaper (₦125 per unit) compared to conventional concrete blocks (₦195 per unit), representing a cost reduction of approximately 36%. The study demonstrates that plastic–sand interlocks offer economic, environmental, and waste management benefits, making them suitable for sustainable construction applications.